Eerste treë in die ontwerp van 'n gereformeerde litugiese simboliek - MU Strauss (Acta Theologica)
This article seeks to emphasize the use of symbols within the workshop service in a reformed liturgical tradition. It points out that the times in which we live have made a reassessment of the use of symbols a pressing priority. The possibilities offered by reformed liturgy are scrutinized. Norms which can be used in determining the usefulness of symbols in reformed workshop service are described. The conclusion reached is that reformed liturgy offers scope for the utilization of various forms of symbolism